The Candida glabrata Upc2A transcription factor is a global regulator of antifungal drug resistance pathways. - Bao Gia Vu (Public Library of Science (PLoS), 2021)
The most commonly used antifungal drugs are the azole compounds, which interfere with biosynthesis of the fungal-specific sterol: ergosterol. The pathogenic yeast Candida glabrata commonly acquires resistance to azole drugs like fluconazole via mutations in a gene encoding a transcription factor called PDR1. These PDR1 mutations lead to overproduction of drug transporter proteins like the ATP-binding cassette transporter Cdr1. In other Candida species, mutant forms of a transcription factor called Upc2 are associated with azole resistance, owing to the important role of this protein in control of expression of genes encoding enzymes involved in the ergosterol biosynthetic pathway. Recently, the C. glabrata Upc2A factor was demonstrated to be required for normal azole resistance, even in the presence of a hyperactive mutant form of PDR1. Using genome-scale approaches, we define the network of genes bound and regulated by Upc2A. By analogy to a previously described hyperactive UPC2 mutation found in Saccharomyces cerevisiae, we generated a similar form of Upc2A in C. glabrata called G898D Upc2A. Analysis of Upc2A genomic binding sites demonstrated that wild-type Upc2A binding to target genes was strongly induced by fluconazole while G898D Upc2A bound similarly, irrespective of drug treatment. Transcriptomic analyses revealed that, in addition to the well-described ERG genes, a large group of genes encoding components of the translational apparatus along with membrane proteins were responsive to Upc2A. These Upc2A-regulated membrane protein-encoding genes are often targets of the Pdr1 transcription factor, demonstrating the high degree of overlap between these two regulatory networks. Finally, we provide evidence that Upc2A impacts the Pdr1-Cdr1 system and also modulates resistance to caspofungin. These studies provide a new perspective of Upc2A as a master regulator of lipid and membrane protein biosynthesis.